On performance of a weighted cooperative spectrum sensing with censoring of cognitive radios in Rayleigh fading. (1st January 2014) - Nallagonda, Srinivas; Roy, Sanjay Dhar; Kundu, Sumit
In this paper, the performance of a weighted cooperative spectrum sensing (WCSS) scheme with censoring of cognitive radios (CRs) in Rayleigh fading is analysed. CRs which employ energy detectors (EDs) are censored depending on the quality of reporting channels. Each CR makes a hard decision about primary user (PU) using EDs and transmits the information to FC using BPSK signalling if that CR is selected to transmit. The weight factors of selected CRs are chosen based on the average SNR profile of the CR and integrated with decisions sent by the corresponding CRs at FC. Combined effects of censoring and SNR-based WCSS have been evaluated and compared with conventional CSS scheme. We develop a simulation framework for evaluating the performance of WCSS and CCSS with censoring in terms of missed detection and total error probabilities for various values of network parameters under perfect and imperfect channel estimation.